Original paperSPECIFIC SITES OF BONE EXPANSION DEPEND ON THE LEVEL OF VOLLEYBALL PRACTICE IN PREPUBESCENT BOYS - Chaari, H.; Zouch, M.; Zribi, A.; Bouajina, E.; Zaouali, M.; Tabka, Z. (Biology of Sport, 2013)
The purpose of this study was to investigate the effect of 18 months of high and low levels of volleyball practice on bone acquisition. 130 prepubescent boys (mean age 11.4 ± 0.7) were divided into a high-level training group (HLG), low-level training group (LLG), and controls. Bone mineral content (BMC) and bone area at the whole body, lumbar spine L2-L4, femoral neck of the dominant leg, and right and left radius were measured using dual-photon X-ray absorptiometry. Enhanced BMC resulted from high-training volleyball activity in all measured sites except the third left and right distal radius, which is not modified by low-level training in prepubescent players but it was accompanied by a bone area expansion in radius and weight-bearing sites for the HLG, and in legs, whole right and left radius for the LLG. Significant improvement of skeletal tissues is associated with the intensity and duration of volleyball training.